2020
DOI: 10.3390/w12010189
|View full text |Cite
|
Sign up to set email alerts
|

Modelling Impacts of a Municipal Spatial Plan of Land-Use Changes on Surface Water Quality—Example from Goriška Brda in Slovenia

Abstract: Intensive agriculture causes nutrient leaching and accelerates erosion processes, which threatens the good quality status of surface waters, as proposed by the European Union (EU) Water Framework Directive. The purpose of this study was to define the impact of two alternative agricultural land-use change scenarios defined in a Municipal Spatial Plan on surface water quality by using the Agricultural Policy/Environmental eXtender (APEX) model. As experimental area, we chose a small Kožbanjšček stream catchment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 40 publications
(46 reference statements)
2
11
0
Order By: Relevance
“…Our findings agree with other previous studies [73,74] conducted in various watersheds in China, where the increase in woodland resulted in a lower runoff and water discharge. Elsewhere, authors reported the reduction in forest cover driven by human activities as the main cause of increases in surface runoff and flood peak discharge [75][76][77]. Overall, our results demonstrated that the changes in land cover driven by afforestation activities (e.g., GTGP and NFCP) across the two mountainous catchments were probably the main cause of decreasing flood peak discharge during the 1990-2016/2017.…”
Section: Impact Of Reforestation Driven Lulc Changes On Flood Peak DIsupporting
confidence: 55%
See 1 more Smart Citation
“…Our findings agree with other previous studies [73,74] conducted in various watersheds in China, where the increase in woodland resulted in a lower runoff and water discharge. Elsewhere, authors reported the reduction in forest cover driven by human activities as the main cause of increases in surface runoff and flood peak discharge [75][76][77]. Overall, our results demonstrated that the changes in land cover driven by afforestation activities (e.g., GTGP and NFCP) across the two mountainous catchments were probably the main cause of decreasing flood peak discharge during the 1990-2016/2017.…”
Section: Impact Of Reforestation Driven Lulc Changes On Flood Peak DIsupporting
confidence: 55%
“…Our findings agree with other previous studies [73,74] conducted in various watersheds in China, where the increase in woodland resulted in a lower runoff and water discharge. Elsewhere, authors reported the reduction in forest cover driven by human activities as the main cause of increases in surface runoff and flood peak discharge [75][76][77].…”
Section: Impact Of Reforestation Driven Lulc Changes On Flood Peak DImentioning
confidence: 99%
“…Turbidity is directly related to the mean slope which may be due to soil erosion. Village biome is positively linearly related with hardness, COD, BOD, N, Cu, Mn and Pb while it is negatively correlated with DO which may due to intense human activities [27]. EC, Cr, Cd and B have positive relationship with the top gravel and top sand.…”
Section: Riparian Buffer Scalementioning
confidence: 95%
“…The SWAT model was developed to predict the impact of land management practices on water, sediments and agricultural chemical yields in ungauged river basins [14]. The model is widely used in hydrological [8,26] and water-quality analyses at the basin scale [27,28] to assess the impact of land-use changes or climate changes on surface waters [19,29].…”
Section: Quantifying Point and Non-point Source Pollutionmentioning
confidence: 99%
“…Conceptual models, such as the Soil and Water Assessment Tool (SWAT) [14], Annualized Agricultural Non-Point Source (AnnAGNPS) [15] or GREEN-Rgrid [16], are generally complex, their use requiring a large amount of data and a specific knowledge of the processes acting in the study area [17]. These models provide more detailed results, at different time and spatial scales, and offer the possibility of simulating the impacts of climate change [18], land-use change and of best management practices (BMPs) [19]. In addition, conceptual models are able to quantify the impact of point sources on surface waters.…”
Section: Introductionmentioning
confidence: 99%